Novel catalysts for valorization of biomass to value-added chemicals and fuels - Lucas, Nishita; Kanna, Narasimha Rao; Nagpure, Atul S.; Kokate, Ganesh; Chilukuri, Satyanarayana V. (Journal of Chemical Sciences, 2014)
Key furan compounds such as 5-hydroxymethylfurfural (HMF), 2,5-furandicarboxylic acid (FDCA) and 2,5-dimethylfuran (DMF) were synthesized from renewable feedstocks. Dehydration of fructose was carried out in biphasic conditions employing several solid acid catalysts by targeting selective formation of HMF. Its selectivity is linearly dependent on total acidity clearly revealing that lower acidity favours selective formation of HMF. Oxidation and hydrogenolysis of HMF has been explored using 2 wt% Ru-K-OMS-2. The catalysts used for each transformation were subjected to detailed characterization using XRD, BET surface area, temperature-programmed desorption and transmission electron microscopy. The effect of various reaction parameters was also investigated for obtaining high yields of desired chemical intermediates. High FDCA yields of 93.4 mol% and 66 mol% were achieved in alkaline and base-free conditions, respectively. The 2 wt% Ru-K-OMS-2 is a versatile catalyst as it also catalyses HMF hydrogenolysis giving 33 mol% of DMF. Thus, utility of various novel materials as catalysts has been demonstrated in the multistep transformations of hexoses to furan-based fuels and chemicals.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: 2; 5-dimethylfuran; 5-furan dicarboxylic acid; 5-hydroxymethyl furfural; dehydration; fructose